A SURVEILLANCE MODEL OF SHARK SPECIES UTILIZATION AT CILACAP OCEAN FISHING PORT USING SYSTEMS APPROACH - Nanang Priyanto; Tri Wiji Nurani; Iin Solihin (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Shark resources are highly vulnerable to overfishing pressure. The conservation status of several shark species in Indonesia is listed in the Red List of the International Union for Conservation of Nature (IUCN) and Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). However, violations of laws and regulations related to the utilization of shark species in Indonesia still occur. These conditions necessitate an effective monitoring and surveillance system to support the sustainable and responsible management of shark species. This study aims to develop a surveillance model for utilizing shark species at the Cilacap Oceanic Fishing Port using a systems approach. The stages of the systems approach applied in this study include needs analysis, problem formulation, system identification, and system modeling. The results reveal that the current surveillance system for shark utilization still faces various challenges that hinder its effectiveness. These issues include a lack of synergy among mandate holders, weak law enforcement, insufficient institutional support, misalignment between existing standard operating procedures and budget allocations with actual needs, limited capacity of fisheries inspectors, low awareness and understanding of legal obligations, suboptimal use of surveillance facilities and infrastructure, and the continued occurrence of unreported fishing. In response to these issues, this study proposes a surveillance model that integrates four sub-models: (1) the regulatory and institutional sub-model, (2) the surveillance procedures and budget sub-model, (3) the human resources sub-model, and (4) the facilities and infrastructure sub-model. This integrated model is expected to address the root causes of the problems and enhance the overall effectiveness of shark utilization surveillance. Key words: sharks resources, surveillance of fish species, modeling system